Renal Spindle Cell Tumor with Thrombus Extension into the Inferior Vena Cava and the Right Atrium Depicted by PET/CT Scan - Sweedat, Deya' Aldeen; Al-Hajaj, Nabeela; Khzouz, Jakub; Al-Ibraheem, Akram (World Journal of Nuclear Medicine, 2022)
Tumor thrombus (also called intravascular tumor extension) can be defined as tumor extending into vessel; typically a vein, it occurs in a lot of malignancies like hepatocellular carcinoma, Wilms tumor, and others.1 Tumor thrombus has been reported to demonstrate increase in fluorine-18 fluorodeoxyglucose (FDG) uptake that would differentiate it from the benign bland thrombus which would not take up FDG on positron emission tomography/computed tomography (PET/CT) scan.1 We present a case of spindle cell sarcoma of right kidney whose baseline contrast-enhanced CT revealed a mass replacing the right kidney and right renal vein associated with thrombus in the inferior vena cava (IVC). 18F-FDG PET/CT imaging was done that revealed an FDG-avid hypermetabolic malignant right renal mass with hypermetabolic IVC thrombus extending to the right atrium.
Keywords: tumor thrombus; PET/CT; spindle cell sarcoma; 18F-FDG